Implementation of the e-SUS Primary Care system: Impact on the routine of Primary Health Care professionals - Tatiele Estefâni Schönholzer; Ione Carvalho Pinto; Fabiana Costa Machado Zacharias; Rodrigo André Cuevas Gaete; Maria Del Pilar Serrano-Gallardo (Universidade de São Paulo, 2021)
Objective: to understand how the implementation of the e-SUS Primary Care system has been processed and its impact on the daily life of the health teams. Method: a qualitative research study, conducted in a municipality in the inland of the state of São Paulo with professionals who work in Primary Health Care and use the e-SUS Primary Care system as a work tool. Semi-structured interviews and thematic data analysis were used with Kotter's three-phase approach. Results: a total of 17 professionals, nurses, physicians, dentists and community agents were interviewed. The implementation of e-SUS Primary Care and its impact on the daily life of health teams were understood in terms of mandatory implementation; weaknesses for implementation, such as absence of material resources and implicit imposition for the use of the system; fragile training for deployment and learning from experience. Conclusion: a harmful incentive process was observed, conducted from the perspective of institutional pressure, use of the system to justify the work performed and, on the other hand, there was the creation of collaborative learning mechanisms between the teams.